Olympic speed skating and why all ice is not created equal - Stefani, R. (Significance, 2014)
The Sochi Olympics added another chapter to the history of Olympic speed skating. An Olympic champion succeeds because of physique, training and efficiency, which in turn, depends on coaching, technique, equipment (drag-reducing suits and clap skates) and ice conditions. Of those factors, ice conditions can change the most from one Games to the next. Ice technicians at Sochi controlled temperature, humidity and ice hardness. But how do their efforts compare with their counterparts from the past?